The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2147/dmso.s330700
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL8/Betatrophin Improves Glucose Tolerance in Older Mice and Metabolomic Analysis Reveals Its Role in Insulin Resistance in HepG2 Cells

Abstract: Background: Insulin resistance is a determining factor in the pathophysiology of type 2 diabetes mellitus (T2DM). Angiopoietin-like protein 8 (ANGPTL8, also known as betatrophin), associated with glucose homeostasis and lipid metabolism, has attracted attention. But its mechanism in glucose metabolism remains unclear. This study aimed to explore the effect of ANGPTL8/betatrophin on glucose tolerance in Kunming (KM) mice of different ages and metabolic profiles in insulin-resistant HepG2 cells. Our study may pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 49 publications
(70 reference statements)
3
7
0
Order By: Relevance
“…Increased maternal serum ANGPTL8 levels were observed in pregnant women relative to non-pregnancy women, which was consistent with the findings of Trebotic et al [ 22 ]. However, the current study showed a decreased level of ANGPTL8 in GDM group compared with NGT group, which was inconsistent with the results from Huang et al [ 11 ] and Erol et al [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Increased maternal serum ANGPTL8 levels were observed in pregnant women relative to non-pregnancy women, which was consistent with the findings of Trebotic et al [ 22 ]. However, the current study showed a decreased level of ANGPTL8 in GDM group compared with NGT group, which was inconsistent with the results from Huang et al [ 11 ] and Erol et al [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…The population difference (Turkish vs. Chinese) may also contribute to the differences observed in Erol et al Interestingly, reduced placental ANGPTL8 protein expression was observed for the first time in GDM patients compared to NGT pregnant women. Since ANGPTL8 is known to reduce maternal serum TG levels [ 23 ] and improve glucose tolerance [ 22 ], the increased circulating ANGPTL8 levels in NGT objects may be a compensation to pregnancy-induced metabolic changes, while the GDM patients may have entered a decompensated state in ANGPTL8 synthesis. The placenta plays many important roles during pregnancy, including maintaining normal fetal physiology and protecting the fetus, as well as providing oxygen and nutrients for fetal development and growth [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results are presented in table.1, for demographic data in controls and T2DM patients, showed a nonsignificant difference (p-value = 0.185 and 0.288) in age and BMI in patients compared with a control. In the current research, our data that values are given in Table 1, are agreement with other studies in T2DM group as compared with controls [1], [11], [15].…”
Section: Laboratory and Clinical Characteristics: Comparison Of Demog...supporting
confidence: 92%
“…ANGPTL8 levels in the blood were found to be significantly higher in patients than in control subjects [10]. Other studies have also found that ANGPTL8 levels are increased in patients with T2DM [2], [11]- [16]. Furthermore, in patients, several studies have found a link between blood glucose, (HOMA-IR), and ANGPTL8 [12], [17].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation